PENGARUH PEMBERIAN BOTOL MINUM DENGAN STIKER BERKARAKTER PADA ANAK USIA PRASEKOLAH UNTUK PEMENUHAN KEBUTUHAN CAIRAN PADA ANAK - riamah riamah; Awaluddin Awaluddin; Anita Syarifah; Khasmayusi Khasmayusi (LPPM Universitas Abdurrab, 2023)
Children are very susceptible to large fluid losses, this is because children are susceptible to diseases, such as fever and diarrhea. The aim of the study was to determine the effect of giving drinking bottles with character stickers to preschool-aged children to meet the needs of fluids in children. Research design with quasi-experimental. This research was conducted with a sample of 30 people, 15 people in the intervention group and 15 people in the control group. The intervention group was given drinking bottles with character stickers while the control group was not given. The measurement tool is the amount of fluid intake every 24 hours in milliliters (ml). Data analysis using unpaired T test, obtained the amount of fluid intake after being given a drinking bottle with a post-test character sticker in the experimental group was 1290 ml, while the fluid intake in the control group was 896.67 ml. The results of the statistical test obtained a p value of 0.000. It can be concluded that there is a significant effect on the amount of fluid intake after being given a drink bottle with a sticker with a character between the experimental and control groups.